Professional responsibility and conscientiousness of civil servants at different stages of professional growth - Oleh Anatolyovych Zarichanskyi; Valerii Vasylovych Sokurenko; Olena Oleksandrivna Yevdokimova (Insight: the psychological dimensions of society, 2023)
The article presents findings of a study of civil servants’ professional responsibility and conscientiousness in the context of their professional activities. The purpose of the paper is to analyze the specifics of professional activity and conscientiousness of civil servants at different stages of their professional growth. Methods: the questionnaire “Structure and Level of Professional Responsibility” by N. Makeieva (2014) and “The Consciousness Scale” by Melnykov & L. Yampolskyi in the adaptation of I. Furmanov & L. Perhamenshchyk (1998). The empirical study base consisted of civil servants at different stages of professional growth: first-year students (majoring in public management and administration) of higher education institutions; novice civil servants; civil servants with ten or more years of experience. The results of the theoretical study demonstrated how integral characteristics of a qualitative character of conscientiousness and responsibility manifest themselves during professional self-actualization and self-fulfillment. It was empirically established that students majoring in public management and administration are less aware of the importance of their activity and the need for its high-quality and thorough performance and have lower responsibility and concern about performance results. Novice civil servants are less capable of making action plans independently and are less prone to display an active attitude in choosing more optimal ways of solving professional tasks. Civil servants with ten or more years of experience are more inclined to be guided in their professional activities by the law, social and professional requirements, and rules. Conclusions. Although it was empirically established that civil servants with ten or more years of experience have a high level of conscientiousness, while students and novice civil servants have a medium level (concurrently with a significantly higher frequency of a low level). The study highlighted the need to examine the specified characteristics and adopt special programs for their development.